(untitled) (Research, Society and Development, 2024)
Brucellosis is a zoonotic reproductive disease caused by Brucella abortus, which is controlled in the National Plan for the Control and Eradication of Brucellosis and Bovine/Bubal Tuberculosis (PNCEBT). It manifests itself primarily through abortions, generally from the 5th month of pregnancy and the birth of weak calves. The method used in this study was bibliographic review. To carry out this research, a survey of articles found on Google Scholar, SciELO, among others, was carried out. With the aim of addressing the stage of sexual maturity in heifers, as well as the need to keep cattle vaccinations up to date to avoid diseases such as brucellosis. In Brazil, where the disease is endemic, the PNCEBT aims to reduce the prevalence through vaccination and property certification. This provides economic and health benefits, protects human and animal health and strengthens the country’s livestock sector.